Metodologi Pembelajaran Bahasa Arab di Lingkungan Formal: Studi dan Implementasi - Imam Abdul Rouf; Faruq Abdul Muid (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2024)
This study investigates the effectiveness of various teaching methodologies for Arabic language instruction at SMA Terpadu, focusing on how these methodologies impact students' learning outcomes and engagement. The research utilizes a mixed-methods approach, combining qualitative and quantitative data to assess the performance of different pedagogical strategies. The methodologies analyzed include the Communicative Approach, Grammar-Translation Method, Immersive Method, and Total Physical Response (TPR). Through comprehensive document analysis, in-depth interviews with educators, and classroom observations, the study identifies the strengths and weaknesses of each approach. Results indicate that while the Communicative and Immersive methods significantly enhance students' speaking and listening skills, the Grammar-Translation Method remains valuable for grammatical understanding. However, each method also presents specific challenges, such as the need for highly skilled teachers and the varying adaptability of students. The findings highlight the importance of a flexible and contextually appropriate approach to teaching Arabic. Recommendations are provided for optimizing instructional strategies to improve language acquisition and student engagement. This research contributes to a deeper understanding of effective Arabic language teaching practices and offers practical insights for educators and curriculum developers.